2015
DOI: 10.1007/s00330-015-3685-4
|View full text |Cite
|
Sign up to set email alerts
|

Chest Computed Tomography-Based Scoring of Thoracic Sarcoidosis: Inter-rater Reliability of CT Abnormalities

Abstract: Purpose To determine inter-rater reliability of sarcoidosisrelated computed tomography (CT) findings that can be used for scoring of thoracic sarcoidosis. Materials and methods CT images of 51 patients with sarcoidosis were scored by five chest radiologists for various abnormal CT findings (22 in total) encountered in thoracic sarcoidosis. Using intra-class correlation coefficient (ICC) analysis, inter-rater reliability was analysed and reported according to the Guidelines for Reporting Reliability and Agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Irreversible lesions include honeycombing, traction bronchiectasis and emphysematous bubbles [24]. Several HRCT scores have been developed to correlate the imaging manifestations with the results of respiratory function tests in pulmonary sarcoidosis [25,26].…”
Section: Ct In Pulmonary Sarcoidosis Imaging Findings and Classificamentioning
confidence: 99%
See 1 more Smart Citation
“…Irreversible lesions include honeycombing, traction bronchiectasis and emphysematous bubbles [24]. Several HRCT scores have been developed to correlate the imaging manifestations with the results of respiratory function tests in pulmonary sarcoidosis [25,26].…”
Section: Ct In Pulmonary Sarcoidosis Imaging Findings and Classificamentioning
confidence: 99%
“…A recent HRCT score based on the presence of ground glass opacities, thickening of the interlobular septa and parenchymal consolidations can allow the quantification of the disease activity and predict the variation of forced vital capacity after a year of therapy [25,26]. Walsh et al reported that both the visual assessment of the extent of pulmonary fibrosis and the relationship between the diameter of the pulmonary artery and the diameter of the ascending aorta on HRCT can provide useful information about the prognosis of sarcoidosis.…”
Section: Ct In Pulmonary Sarcoidosis Imaging Findings and Classificamentioning
confidence: 99%
“…Numerous CT-based scoring systems have been developed for evaluation of the correlation between CT findings and pulmonary function test results in pulmonary sarcoidosis (24,25). A recent CT scoring system based on nodularity, groundglass opacification, interlobular septal thickening, and consolidation was reported to allow quantification of disease activity and prediction of forced vital capacity response to therapy at 1 year (24).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…This is due in part to the diverse and heterogeneous patterns present on chest HRCT in sarcoidosis, often with multiple patterns noted on one CT. These complexities result in high inter- and intra-rater variation (11). More automated systems that quantify sarcoidosis chest HRCT could decrease these sources of variation.…”
Section: Introductionmentioning
confidence: 99%